The Impact of Youth Unemployment on Political Mobilization in Pakistan: Implications for Political Stability, Social Peace, and Policy Reforms (2020–2025) - Ali Nawaz Soomro; Dr. Dilawar Khan; Sonia Ambreen (Dialogue Social Science Review (DSSR), 2025)
Youth unemployment remains one of the most pressing socio-economic challenges in Pakistan, significantly influencing the country’s political landscape. This study explores the complex relationship between youth unemployment and political mobilization in Pakistan during the period 2020 to 2025, examining its implications for political stability, peace, and policy reforms. Unemployed youth, often marginalized economically and socially, increasingly engage in political activism, protests, and organized movements as a response to their disenfranchisement. This research investigates how such mobilization affects Pakistan’s political stability and social cohesion, particularly amid a volatile domestic environment marked by economic uncertainty and rising political polarization. The study employs a mixed-methods approach, combining quantitative data analysis of unemployment rates and protest activities with qualitative interviews of youth activists, policymakers, and experts. It aims to identify the pathways through which unemployment drives political engagement and the forms this engagement takes—ranging from peaceful advocacy to potentially disruptive protests. Furthermore, the research assesses government responses and policy initiatives aimed at addressing youth unemployment and their effectiveness in mitigating political unrest. This research fills a critical gap in existing literature by linking youth economic disenfranchisement directly to political behavior and its broader consequences for Pakistan’s stability and peace. It highlights how unresolved youth unemployment can exacerbate social tensions and contribute to cycles of instability if not addressed through inclusive and sustainable policy reforms. The findings are expected to provide valuable insights for policymakers, civil society, and scholars on designing targeted interventions that harness youth energy constructively and foster long-term political stability. By focusing on the 2020–2025 timeframe, this study captures recent developments and trends, offering a timely analysis crucial for Pakistan’s socio-political future.